(untitled) (Journal of the College of Basic Education, 2024)
This study aims to evaluate and study the heavy elements in the soil of Mada’in district to determine its suitability for agricultural investment, as the aim of the study is to find out the extent of soil contamination in Mada’in district with heavy elements, because it has effects on human, animal and plant health, causing diseases and risks if it exceeds the specified proportions. The pollution of the environment with all kinds of air, water or soil is one of the difficulties that we face at the present time, especially in Iraq at the present time in the absence of regulations and laws or non-compliance with them, where all environmental systems are exposed to pollution, in turn, reflected on human, animal and Plant Health, and in this research, the impact of heavy elements on the characteristics of cultivated soils in the Mada’in district, where samples were taken from different areas of soil, where 7 samples were taken from different samples from different Heavy elements such as lead, cadmium, copper, boron and nickel were addressed, and the results showed that there is a temporal and spatial variation in the values of the results, some of them with high percentages, such as Tuwaitha province, and some in arifiyah province, and 7 soil samples were taken from different agricultural provinces in Mada’in district